Winter cover crops in corn and forage sorghum rotations in the Great Plains - Freeman, Oliver W., II (Kansas State University, 2014)
In Kansas, winter cover crops have a new interest with the development of summer crops for biofuel. When a crop is harvested for bioenergy, the residue is removed leaving the soil prone to erosion during the winter. It is possible that the use of winter cover crops may allow for more residue to remain in a field while keeping the soil from blowing. Therefore, the objective of this research was to determine the effect of two winter cover crops on the growth of two biofuel crops, corn (Zea mays L.) and forage sorghum [Sorghum bicolor (L.) Moench] in a corn-forage sorghum rotation. The two cover crops were a legume, Austrian winter pea (Pisum sativum var. arvense Poir.) and winter wheat (Triticum aestivum L.). Control plots were fallowed. The experiment was done for two years (2010 and 2011) at two locations: under rain-fed conditions in Manhattan in the northeastern part of Kansas, where the soil was a Belvue silt loam (coarse-silty, mixed superactive non-acid, mesic Typic Udifluvents) and under irrigated conditions in Tribune in the western part of Kansas, where the soil was a Richfield silt loam (fine, smectitic, mesic Aridic Argiustolls). Two levels of nitrogen were added to the soil: 0 and 101 kg ha[superscript]-1 N. Grain and stover yields of the corn and forage sorghum were determined at harvest of the crops in the fall, and dry matter production of the cover crops was determined at their termination in the springs of 2011 and 2012. Additional nitrogen fertilizer increased grain and stover yields in both growing seasons at both locations, except for Manhattan in 2010. During the second winter of the study, Austrian winter pea did not emerge in Manhattan, probably due to a combination of cold temperatures and drought. Austrian winter pea survived both winters at Tribune. Corn yielded more grain than did the forage sorghum in Manhattan in 2011 and in Tribune in 2011. This suggests that, under both rain-fed and irrigated conditions in Kansas, corn would potentially be more productive for bioenergy production than forage sorghum. The results of the study also showed that winter wheat for both Manhattan, Kansas, and Tribune, Kansas, should be the cover crop chosen, because of its ability to grow well during the off-season of the bioenergy crops and to provide soil cover during winter.
Keywords: Winter cover crops; Agronomy (0285)